Should routine screening for vitamin D deficiency be performed in pregnancy?. Issue 11 (November 2016) - Da Graca Costa, Charmaine Silveira; Hoffmann, Kathryn
Abstract : EVIDENCE‐BASED ANSWER : No. Low vitamin D levels in pregnancy are associated with worse outcomes than no vitamin deficiency; however, supplementation does not conclusively improve outcomes (SOR: B, meta‐analyses of observational studies and RCTs). The Royal College of Obstetricians and Gynaecologists (RCOG) recommends against screening for vitamin D deficiency in pregnancy (SOR: C, expert opinion).